The Effect of Gate Position Start on BMX Cross Athletes' Perception of Anxiety - Rere Anne Marisa Nuraini; Moch. Yamin Saputra; Yopi Kusdinar (Universitas Negeri Semarang, 2025)
Background: Gate startIn BMX Cross, the starting gate is a crucial phase that determines an athlete's strategic position and initial performance. Different starting positions can elicit varying levels of psychological stress, particularly in the form of competitive anxiety. This anxiety has the potential to disrupt an athlete's focus, mental preparedness, and technical effectiveness during the race. This study highlights the influence of starting gate position on BMX Cross athletes' perceptions of anxiety during competition. Objectives:This study aims to analyze the perception of anxiety of BMX Cross athletes.based on the difference in starting positions occupied by each athlete. Method: The method used in this study is descriptive quantitative with the Sport Anxiety Scale-2 (SAS-2) instrument. The sample involved was 30 BMX Cross athletes with a total sampling technique. Data analysis is presented using SPSS version 25. Results: The results of the study indicate that there are differences between starting gate positions on athletes' anxiety perceptions with a significance value of p = 0.004. Conclusion: This study concludes that starting gate positions can significantly influence anxiety perceptions in BMX Cross athletes. Suggestion: This study suggests implementing mental management exercises so that athletes can control the anxiety they experience when under pressure.pressure and athletes can implement it when they compete.